FexBi2Se3 superconductivity, dimensional transport, and high electron mobility are associated with the natural nanostructure of Bi2Se3 single crystals - Zich, Jan; Misek, Martin; Holy, Vaclav; Carva, Karel; Cizek, Jakub; Navrátil, Jiří; Čermák, Patrik; Knotek, Petr; Čermák Šraitrová, Kateřina; Cichon, Stanislav; Hejtmanek, Jiri; Jirak, Zdenek; et al. (American Physical Society, 2023)
In this paper, we report the physical properties of FexBi2Se3 single crystals. Fe-intercalated Bi2Se3 exhibits superconductivity, pronounced Shubnikov-de Haas oscillations, high carrier mobility, and features of two-dimensional (2D) transport in the sample volume for x as low as 0.02. The superconductivity of the samples is limited to the range x = 0.02-0.04. We correlate all the transport properties with structural properties, namely, with mosaic structure of single crystals and point defects. This correlation in the context of the rich literature data allows us to build an intricate physical picture addressing the unique properties of the material under study within the framework of the Bi2Se3 quasi-2D defect structure model. The ultimate aim of this paper is to show that many interesting properties of Bi2Se3 may be associated with inhomogeneous distribution of defects in the volume of the sample, which largely replicates the mosaicity of single crystals.
Supravodivost FexBi2Se3, 2D-transport a vysoká pohyblivost elektronů jsou spojeny s inherentní nanostrukturou monokrystalů Bi2Se3.
Keywords: 1st-principles calculations; topological insulator; symmetry-breaking; state; výpočty 1. principů; topologický izolátor; symetrie